Towards Operationalizing the SRF with a Suite of Indicators within a Monitoring, Evaluation and Learning Framework - CGIAR Indicator Task Force (CGIAR Indicator Task Force, 2016)
Update from the Indicator Task Force: Towards Operationalizing the SRF with a Suite of Indicators within a Monitoring, Evaluation and Learning Framework